Space Breeding: The Next-Generation Crops - Mohanta, Tapan Kumar; Mishra, Awdhesh Kumar; Mohanta, Yugal Kishore; Al-Harrasi, Ahmed (Frontiers in Plant Science, 2021)
Since the beginning of space exploration, researchers have been exploring the role of microgravity, cosmic radiation, and other aspects of the space environment on plant growth and development. To create superior crop varieties and achieve noticeable success in the space environment, several types of research have been conducted thus far. Space-grown plants have been exposed to cosmic radiation and microgravity, which has led to the generation of crop varieties with diverse genotypes and phenotypes arising from different cellular, subcellular, genomic, chromosomal, and biochemical changes. DNA damage and chromosomal aberrations due to cosmic radiation are the major factors responsible for genetic polymorphism and the generation of crops with modified genetic combinations. These changes can be used to produce next-generation crop varieties capable of surviving diverse environmental conditions. This review aims to elucidate the detailed molecular mechanisms and genetic mutations found in plants used in recent space crop projects and how these can be applied in space breeding programmes in the future.